Them Too - Nancy Leong (Washington University Law Review, 2019)
Discussions of sexual misconduct often focus primarily or exclusively on the parties directly involved in sexual behavior. As a result, the discussion generally centers on consent. While consent is critically important, this Article instead focuses on harms to third parties resulting from sexual behavior—regardless of whether that behavior is consensual. Doing so reveals a dynamic that the conversation about sexual misconduct has not yet fully acknowledged: the presence or absence of consent between participants does not determine whether third parties suffer harm. Sexual behavior does not occur in a vacuum. Rather, it occurs in a particular context and often has significant consequences for other individuals beyond the participants in the behavior. Sexual behavior is problematic when it involves what this Article will refer to as an institutional power disparity: that is, one participant has power over the other as a result of their institutional roles. Institutional power disparities are inherent, for example, in sexual behavior involving a supervisor and their subordinate or a professor and their student. Such behavior risks significant harm to third parties within the institution. Third parties may be injured as a result of sexual favoritism. For example, a worker may be passed over for a promotion in favor of a less qualified worker who is having sex with the boss. Or third parties may suffer harm from a sexualized institutional environment. For example, students may avoid professors who are known for pursuing sexual relationships with students or may find it alienating to be viewed as a professor’s prospective sexual partner. And the institution itself may suffer harm when sexual behavior involving an institutional power disparity interferes with worker productivity and morale, or with student learning and intellectual growth. Harm to third parties justifies regulation of sexual relationships in the context of an institutional power disparity. In some circumstances, such relationships should be prohibited so long as the institutional power disparity remains. In other circumstances, careful regulation can mitigate potential harms to third parties and to the institution itself.
Keywords: Third-party harms; Power imbalances; Institutional power disparities; Gender inequality; Title VII; Title IX; Antidiscrimination law; Institutional policies; Sexual misconduct